2022
DOI: 10.7759/cureus.23529
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Functional Outcome Predictors in Patients Undergoing Lumbar Interbody Fusion Surgery: A Single-Centre Analysis

Abstract: Introduction Lumbar interbody fusion is a surgical modality performed in selected patients with low back and radicular pain not responding to medical therapy. We aim to evaluate the main predictors of functional outcome, assessed through Oswestry Disability Index (ODI), in patients submitted to a lumbar interbody fusion. Methods A sample of 33 patients undergoing lumbar interbody fusion at a neurosurgery department between 2017 and 2020 was selected. In order to assess function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Various studies have analysed and compared the preoperative and postoperative functional status of the patients who underwent lumbar interbody fusion [20]. Marques et al in a recent retrospective study of 33 patients who underwent posterior lumbar interbody fusion reported that patients who have a poorer score based on ODI scale preoperatively the more they are likely to benefit from a surgical operation [21]. On the contrary, Abduljabbar FH et al reported that there is no correlation between ODI and the preoperative status [22].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have analysed and compared the preoperative and postoperative functional status of the patients who underwent lumbar interbody fusion [20]. Marques et al in a recent retrospective study of 33 patients who underwent posterior lumbar interbody fusion reported that patients who have a poorer score based on ODI scale preoperatively the more they are likely to benefit from a surgical operation [21]. On the contrary, Abduljabbar FH et al reported that there is no correlation between ODI and the preoperative status [22].…”
Section: Discussionmentioning
confidence: 99%